Immunomodulatory Effects of the Tobacco Defensin NaD1 - Ekaterina I. Finkina; Ivan V. Bogdanov; Olga V. Shevchenko; Serafima I. Fateeva; Anastasia A. Ignatova; Sergey V. Balandin; Tatiana V. Ovchinnikova (MDPI AG, 2024)
Background/Objectives: Defensins are important components of the innate plant immune system, exhibiting antimicrobial activity against phytopathogens, as well as against fungi pathogenic to humans. Along with antifungal activity, plant defensins are also capable of influencing various immune processes, but not much is known about these effects. In this study, we investigated the immunomodulatory effects of the tobacco defensin NaD1, which possesses a pronounced antifungal activity. Methods and Results: We showed that NaD1 could penetrate the Caco-2 polarized monolayer. Using a multiplex assay with a panel of 48 cytokines, chemokines and growth factors, we demonstrated that NaD1 at a concentration of 2 μM had immunomodulatory effects on human dendritic cells and blood monocytes, mainly inhibiting the production of various immune factors. Using the sandwich ELISA method, we demonstrated that NaD1 at the same concentration had a pronounced immunomodulatory effect on unstimulated THP-1-derived macrophages and those stimulated by bacterial LPS or fungal zymosan. NaD1 had a dual effect and induced the production of both pro-inflammatory cytokine IL-1β as well as anti-inflammatory IL-10 on resting and pro-inflammatory THP-1-derived macrophages. We also found that the immunomodulatory effects of the tobacco defensin NaD1 and the pea defensin Psd1 differed from each other, indicating nonuniformity in the modes of action of plant defensins. Conclusions: Thus, our data demonstrated that the tobacco defensin NaD1 exhibits different immunomodulatory effects on various immune cells. We hypothesized that influence on human immune system along with antifungal activity, could determine the effectiveness of this peptide under infection in vivo.